2016
DOI: 10.1088/1674-4527/16/5/080
|View full text |Cite
|
Sign up to set email alerts
|

Quark nova model for fast radio bursts

Abstract: FRBs are puzzling, millisecond, energetic radio transients with no discernible source; observations show no counterparts in other frequency bands. The birth of a quark star from a parent neutron star experiencing a quark nova -previously thought undetectable when born in isolation -provides a natural explanation for the emission characteristics of FRBs. The generation of unstable r-process elements in the quark nova ejecta provides millisecond exponential injection of electrons into the surrounding strong magn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 44 publications
0
25
0
1
Order By: Relevance
“…Based on these typical characteristics, it has been suggested that these sources may originate at cosmological distances, corresponding to redshifts z of 0.5 to 1. If so, the isotropic total energy released in one FRB is inferred to be ∼ 10 38−40 erg, and the peak radio luminosity is estimated to be ∼ 10 42−43 erg s [11], neutron star mergers [12], white dwarf mergers [13], collapsing super-massive neutron stars [14,15], companions of extragalactic pulsars [16], asteroid collisions with neutron stars [17], quark nova [18], and dark matterinduced collapse of neutron stars [19]. All of these models considered FRBs as extragalactic burst sources.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these typical characteristics, it has been suggested that these sources may originate at cosmological distances, corresponding to redshifts z of 0.5 to 1. If so, the isotropic total energy released in one FRB is inferred to be ∼ 10 38−40 erg, and the peak radio luminosity is estimated to be ∼ 10 42−43 erg s [11], neutron star mergers [12], white dwarf mergers [13], collapsing super-massive neutron stars [14,15], companions of extragalactic pulsars [16], asteroid collisions with neutron stars [17], quark nova [18], and dark matterinduced collapse of neutron stars [19]. All of these models considered FRBs as extragalactic burst sources.…”
Section: Introductionmentioning
confidence: 99%
“…This ejecta may be visible following the quark-nova either by interaction with surrounding material as a super-luminous or double-humped supernova, 5,6 or by the decay of unstable r-process isotopes as a fast radio burst. 7 Additional observational evidence for this r-process rich material may exist in the form of gravitationally bound fall-back material surrounding the quark-star. This fall-back material can either form a co-rotating shell, or a Keplerian disk depending on the period of the parent neutron star.…”
Section: Quark-novaementioning
confidence: 98%
“…Models of non-repeating FRBs include a collapse of a neutron star (e.g., Fuller & Ott 2015;Falcke & Rezzolla 2014;Shand et al 2016), NS-asteroid collision (Geng & Huang 2015), pulsar-black hole (BH) interaction (Bhattacharyya 2017), merger of compact objects (e.g., Zhang 2016;Liu et al 2016;Mingarelli et al 2015;Totani 2013;Liu 2018;Li et al 2018;Kashiyama et al 2013;Yamasaki et al 2018), NS-supernova (SN) interaction (Egorov & Postnov 2009), AGN jet-cloud interaction (e.g., Romero et al 2016) and SN remnant powered by a flare from a magnetar (e.g., Popov & Postnov 2010;Lyubarsky 2014;Murase et al 2016).…”
Section: Implications On Frb Modelsmentioning
confidence: 99%